Diversitas Arthropoda Tanah di Lahan Kebakaran dan Lahan Transisi Kebakaran Jalan HM 36 Taman Nasional Baluran - Halli, Mustofa; Agung, I Dewa; Yanuwiadi, Bagyo (Biotropika: Journal of Tropical Biology, 2014)
Aim of this experiment to determine arthropods diversity at HM36 Baluran National park after burned and to know it relation with human activity. This experiment held in November 2013. Taking sample using pit fall trap methods at burned land and transition land after burned with two sampling spot and three pit fall jam for each spot. Sample identified with morphological analyze and abundance measurement, Frequency, relative abundance, frequency abundance, and Â importance value rank. Diversity analyze using Shannon-Wiener index and Bray Curtis Index to determine similarity level for each location. After burned land has 2.05 and 1.04 at transistion land after burned from diversity analyze. Formicidae dominating at every location of sampling. Each location is different each other with only 25% of Bray Curtis analyze measurement. Abiotic and Colony domination effecting diversity level and environment condition. Â  Keyword : Pit fall trap, Importance value rank, Shannon wiener index, Bray Curtis index